2020
DOI: 10.1364/oe.394393
|View full text |Cite
|
Sign up to set email alerts
|

On-chip silicon photonics based grating assisted vibration sensor

Abstract: We present a compact, highly sensitive and scalable on-chip photonic vibration measurement scheme for vibration sensing. The scheme uses a silicon photonic diffraction-grating based sensor integrated underneath a silicon cantilever. We demonstrate a static and dynamic measurement sensitivity (ΔT/Δgap) of 0.6 % change in intensity per nm displacement. The electrostatically driven dynamic response measurement of the grating based sensor shows an excellent agreement with commercial Laser Doppler Vibrometer (LDV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Mere et al [112,113] demonstrated a vibrometer that is used to measure cantilever vibrations (Figure 8). In this configuration, light is sent to the PIC via a grating coupler.…”
Section: Homodyne Pic-based Ldvmentioning
confidence: 99%
See 2 more Smart Citations
“…Mere et al [112,113] demonstrated a vibrometer that is used to measure cantilever vibrations (Figure 8). In this configuration, light is sent to the PIC via a grating coupler.…”
Section: Homodyne Pic-based Ldvmentioning
confidence: 99%
“…This demonstration, however, is limited to measuring the vibration of a close-by and well-aligned cantilever. Mere et al [112,113] demonstrated a vibrometer that is used to measure cantilever vibrations (Figure 8). In this configuration, light is sent to the PIC via a grating coupler.…”
Section: Homodyne Pic-based Ldvmentioning
confidence: 99%
See 1 more Smart Citation